2016
DOI: 10.1021/acs.jnatprod.6b00371
|View full text |Cite
|
Sign up to set email alerts
|

Corallocins A–C, Nerve Growth and Brain-Derived Neurotrophic Factor Inducing Metabolites from the Mushroom Hericium coralloides

Abstract: Three new natural products, corallocins A-C (1-3), along with two known compounds were isolated from the mushroom Hericium coralloides. Their benzofuranone and isoindolinone structures were elucidated by spectral methods. All corallocins induced nerve growth factor and/or brain-derived neurotrophic factor expression in human 1321N1 astrocytes. Furthermore, corallocin B showed antiproliferative activity against HUVEC and human cancer cell lines MCF-7 and KB-3-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 31 publications
4
46
0
Order By: Relevance
“…This indicates that they have the ability to replace the initial requirement for serum trophic factors in neuronal cultures. Consistent with our present study, corallocin A (C3) was shown to induce NGF and BDNF expression in astrocytes (Wittstein et al 2016). Several compounds from H. erinaceum have been suggested to improve brain function via NGF-related activity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This indicates that they have the ability to replace the initial requirement for serum trophic factors in neuronal cultures. Consistent with our present study, corallocin A (C3) was shown to induce NGF and BDNF expression in astrocytes (Wittstein et al 2016). Several compounds from H. erinaceum have been suggested to improve brain function via NGF-related activity.…”
Section: Discussionsupporting
confidence: 91%
“…C2 and C4 were obtained from A2D by recrystallization followed by semi-preparative HPLC eluting with MeCN. The structures of isolated compounds were identified as N-de phenylethyl isohericerin (C1), hericene A (C2), corallocin A (C3) and 4-[3′,7′′-dimethyl-2′,6′-octadienyl]-2-formyl-3-hydroxy-5-methyoxybenzylalcohol (C4) by the analysis of the spectroscopic data and comparison with literature values (Li et al 2015;Wittstein et al 2016).…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…Hericenones C-E from H. Erinaceus markedly potentiated the neurite outgrowth of PC12 cells in the presence of NGF (5 ng/mL) [ 32 ]. Treatment of PC12 cells with corallocins A- or C-conditioned media produced by 1321N1 astrocytes resulted in significant increase of neurite outgrowth [ 33 ]. Furthermore, it was demonstrated that increasing neurite outgrowth activity in PC12 cells by the above compounds exhibited a strong correlation with the stimulation of NGF synthesis [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Hericium coralloides is a white fleshy and coral-like fungus growing mostly on dead or rotting hardwood (McCracken and Dodd, 1971). The fruiting bodies of H. coralloides are edible and considered as a delicious mushroom, and it has long been used in traditional Chinese medicine (TCM) to treat diseases (Wittstein et al 2016). In this study, we present the complete mitochondrial genome of Hericium coralloides (GenBank accession no: KY007042, NCBI Reference Sequence: NC_033903.1).…”
Section: Mitogenome Announcementmentioning
confidence: 99%